2016
DOI: 10.1590/s1677-5538.ibju.2014.0593
|View full text |Cite
|
Sign up to set email alerts
|

White blood cell counts and neutrophil to lymphocyte ratio in the diagnosis of testicular cancer: a simple secondary serum tumor marker

Abstract: Purpose The aim of the study was to investigate white blood cell counts and neutrophil to lymphocyte ratio (NLR) as markers of systemic inflammation in the diagnosis of localized testicular cancer as a malignancy with initially low volume.Materials and Methods Thirty-six patients with localized testicular cancer with a mean age of 34.22±14.89 years and 36 healthy controls with a mean age of 26.67±2.89 years were enrolled in the study. White blood cell counts and NLR were calculated from complete blood cell cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
38
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 19 publications
7
38
0
1
Order By: Relevance
“…Several studies have also shown that low lymphocyte counts are significantly associated with poor survival in lung cancer patients 19, 20. Therefore, peripheral blood lymphocyte counts have been used as an important constituent marker not only in PLR but also in numerous prognostic indicators, such as NLR and the prognostic nutritional index 6, 7, 8…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have also shown that low lymphocyte counts are significantly associated with poor survival in lung cancer patients 19, 20. Therefore, peripheral blood lymphocyte counts have been used as an important constituent marker not only in PLR but also in numerous prognostic indicators, such as NLR and the prognostic nutritional index 6, 7, 8…”
Section: Discussionmentioning
confidence: 99%
“…This is the first study to report that PLR is a more useful prognostic indicator for NSCLC patients treated with surgery and adjuvant chemotherapy compared to all surgical patients. Biomarkers of inflammation, such as NLR or PLR, have been associated with the prognosis of patients with various cancers 7,8 and have specifically been shown to be predictive markers of postoperative prognosis in gastric cancer, 14 cholangiocarcinoma, 15 hepatocellular carcinoma, 8 and primary lung cancer. 16 Some studies have reported that hostderived inflammation, immune response, and coagulation status play important roles in tumor growth, invasion, angiogenesis, and metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We read the article by Yuksel et al (1) entitled “White blood cell counts and neutrophil to lymphocyte ratio in the diagnosis of testicular cancer: a simple secondary serum tumor marker” published in your journal. This is a very interesting study which is very well-designed and presented.…”
mentioning
confidence: 99%
“…Routine peripheral blood counts may be beneficial in prognosis and diagnosis of many disorders, involving testicular cancer (1, 613). NLR is measured by dividing the number of neutrophils by the number of lymphocytes.…”
mentioning
confidence: 99%